2004
DOI: 10.1111/j.1365-2990.2004.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of insulin‐like growth factor‐I and ‐II mRNA expression in medulloblastoma

Abstract: Insulin-like growth factors (IGFs) play an important role in tumour growth and development. We hypothesized that this is also the case for medulloblastomas, which are highly malignant cerebellar brain tumours usually occurring in children. In these tumours the expression patterns of IGF-I and -II mRNA were studied. Tumour specimens obtained from 12 children and two adults at diagnosis were hybridized in situ with digoxigenin-labelled cRNA probes for hIGF-I and hIGF-II mRNAs. In all cases, tumour cells showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The IGF system is known to have an important function in the development and growth of the CNS [138] and also appears to play a pivotal role in the development and growth of medulloblastomas and ependymomas [139][140][141][142]. A microarray study identified overexpression of IGF2 by desmoplastic medulloblastomas [143], and similar results were obtained for ependymomas, although not all the samples analyzed were pediatric cases [144].…”
Section: Tumors Of the Central Nervous System (Cns)supporting
confidence: 75%
See 1 more Smart Citation
“…The IGF system is known to have an important function in the development and growth of the CNS [138] and also appears to play a pivotal role in the development and growth of medulloblastomas and ependymomas [139][140][141][142]. A microarray study identified overexpression of IGF2 by desmoplastic medulloblastomas [143], and similar results were obtained for ependymomas, although not all the samples analyzed were pediatric cases [144].…”
Section: Tumors Of the Central Nervous System (Cns)supporting
confidence: 75%
“…A microarray study identified overexpression of IGF2 by desmoplastic medulloblastomas [143], and similar results were obtained for ependymomas, although not all the samples analyzed were pediatric cases [144]. Similarly, abundant expression of IGF1 and IGF2 mRNA was demonstrated in pediatric medulloblastoma tumors [142]. Furthermore, the phosphorylated activated form of IGF1R has been detected in medulloblastoma cell lines and biopsies from pediatric patients [139,140].…”
Section: Tumors Of the Central Nervous System (Cns)mentioning
confidence: 59%
“…Insulin-like growth factor 2 ( igf2 ) is expressed at high levels compared to normal tissue in both MB and RMS in ptc1 +/- mice (16) and in humans (19, 20, 21, 22). Hahn et al demonstrated that igf2 is critical for the formation of both MB and RMS in ptc1 +/- mice.…”
Section: Introductionmentioning
confidence: 99%
“…The insulin‐like growth factor (IGF) system plays an important role in the regulation of the development and growth of the CNS,3 but also that of medulloblastoma and ependymoma 4–8. This complex system consists of 2 mitogenic and antiapoptotic peptides, IGF‐I and IGF‐II, 2 IGF‐receptors (IGF‐IR and IGF‐IIR), 6 IGF binding proteins (IGFBP1‐6), several IGFBP cell surface receptor proteins and IGFBP proteases 9.…”
mentioning
confidence: 99%